How is our mobility affected as we age? Findings from a 934 users field study of older adults conducted in an urban Asian city - TAN, Yi Zhen (Institutional Knowledge at Singapore Management University, 2024)
In this paper, we analyze the results of a large study involving 934 older adults living in an urban Asian city that collected their mobility patterns, in the form of logged GPS data, along with a multitude of demographic and health data. We show that mobility, in terms of average distance travelled per day, is greatly affected by age and by employment status. In addition, other factors such as type of day, household size, physical and financial conditions and the onset of retirement also play a significant role in determining the mobility of an individual. These results will have high value to any researcher understanding and attempting to transform the lifestyle of older adults.